TLR2 2258 G>A single nucleotide polymorphism and the risk of congenital infection with human cytomegalovirus. Issue 1 (December 2017) - Wujcicka, Wioletta; Paradowska, Edyta; Studzińska, Mirosława; Wilczyński, Jan; Nowakowska, Dorota
Abstract Background Human cytomegalovirus (HCMV) is responsible for the most common intrauterine infections, which may be acquired congenitally from infected pregnant woman to fetus. The research was aimed to estimate the role of three single nucleotide polymorphisms (SNPs) located inTLR2 gene, and the common contribution ofTLR2, and previously studiedTLR4 andTLR9 SNPs, to the occurrence of congenital HCMV infection in fetuses and newborns. Methods The study was performed in 20 Polish fetuses and newborns, congenitally infected with HCMV, and in 31 uninfected controls, as well as with participation of pregnant women, the mothers of 16 infected and 14 uninfected offsprings. Genotypes inTLR2 SNPs were determined, using self-designed nested PCR-RFLP assays, and confirmed by sequencing. The genotypes were tested for Hardy-Weinberg (H-W) equilibrium, and for their relationship with the development of congenital cytomegaly, using a logistic regression model. The common influence ofTLR2, TLR4 andTLR9 SNPs on the occurrence of congenital disease was estimated by multiple-SNP analysis. Results Distribution of the genotypes and alleles inTLR2 1350 T>C and 2029 C>T SNPs was similar between the studied groups of fetuses and neonates. In case of 2258 G>A polymorphism, the GA heterozygotic status was significantly more frequent in the infected cases than among the uninfected individuals (25.0% vs. 3.2%, respectively), and increased the risk of HCMV infection (OR 10.00, 95% CI 1.07–93.44;P ≤ 0.050). Similarly, the A allele within 2258 G>A polymorphism was significantly more frequent among the infected offsprings than in the uninfected ones (12.5% vs. 1.6%;P ≤ 0.050). Complex AA variants for bothTLR2 2258 andTLR9 2848 G>A polymorphisms, were estimated to be at increased risk of congenital HCMV infection (OR 11.58, 95% CI 1.19–112.59;P ≤ 0.050). Additionally, significant relationships were observed between the occurrence of complex AA or GA variants for bothTLR2 andTLR9 SNPs and the increased viral loads, determined in fetal amniotic fluids and in maternal blood or urine specimens (P ≤ 0.050). Conclusions Among variousTLR2, TLR4 andTLR9 polymorphisms, TLR2 2258 G>A SNP seems to be an important factor associated with increased risk of congenital HCMV infection in Polish fetuses and neonates.